2018
DOI: 10.1016/j.cmi.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Cutibacterium acnes molecular typing: time to standardize the method

Abstract: There is an obvious need to create a consensus about molecular typing methods for C. acnes. This standardization will facilitate the comparison of results between one article and another, and also the interpretation of clinical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Cutibacterium acnes is an important member of the human skin microbiota (Christensen & Brüggemann, 2014). Although the taxonomy of this species was recently revised (Scholz & Kilian, 2016), C. acnes remains heterogeneous and has been sub-divided in six principal phylotypes (Dagnelie et al, 2018). In skin, bacteria such as the RT4 HL045PA1/HM-516 (phylotype IA 1 ) appear predominantly associated to acne, whereas strains such as the RT6 HL110PA3/ HM-554 (Phylotype II) are found on healthy skin areas (Fitz-Gibbon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cutibacterium acnes is an important member of the human skin microbiota (Christensen & Brüggemann, 2014). Although the taxonomy of this species was recently revised (Scholz & Kilian, 2016), C. acnes remains heterogeneous and has been sub-divided in six principal phylotypes (Dagnelie et al, 2018). In skin, bacteria such as the RT4 HL045PA1/HM-516 (phylotype IA 1 ) appear predominantly associated to acne, whereas strains such as the RT6 HL110PA3/ HM-554 (Phylotype II) are found on healthy skin areas (Fitz-Gibbon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, this species remains itself highly heterogeneous with six main phylotypes IA1, IA2, IB, IC, II, and III (Dagnelie, Khammari, Dréno, & Corvec, 2018;McDowell, 2017). Cutibacterium acnes genome is characterized by a large stable core (>80% of chromosomal DNA) whereas 7%-11% of coding sequences should be species or even strain specific (Brzuszkiewicz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reclassification from Propionibacterium acnes to Cutibacterium acnes was proposed in 2016 . A standardized method to perform molecular typing of C. acnes , according to the degree of resolution needed (phylotypes, clonal complexes, single‐locus sequence typing), has been recently suggested …”
mentioning
confidence: 99%
“…1 A standardized method to perform molecular typing of C. acnes, according to the degree of resolution needed (phylotypes, clonal complexes, single-locus sequence typing), has been recently suggested. 2 In the first article of this supplement, the authors review the most recent data on C. acnes and its involvement in etiopathogenesis of acne. 3 New findings on C. acnes have revealed that, contrary to what was previously thought, its proliferation is not the trigger of acne.…”
mentioning
confidence: 99%